2017
DOI: 10.1038/srep40616
|View full text |Cite
|
Sign up to set email alerts
|

Chromatin organization revealed by nanostructure of irradiation induced γH2AX, 53BP1 and Rad51 foci

Abstract: The spatial distribution of DSB repair factors γH2AX, 53BP1 and Rad51 in ionizing radiation induced foci (IRIF) in HeLa cells using super resolution STED nanoscopy after low and high linear energy transfer (LET) irradiation was investigated. 53BP1 and γH2AX form IRIF with same mean size of (540 ± 40) nm after high LET irradiation while the size after low LET irradiation is significantly smaller. The IRIF of both repair factors show nanostructures with partial anti-correlation. These structures are related to d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
87
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(99 citation statements)
references
References 35 publications
(66 reference statements)
12
87
0
Order By: Relevance
“…Despite numerous studies regarding the involvement of gH2AX in DNA repair, the nanoscale organization of gH2AX and DDR proteins within IR-induced foci remains largely unknown because of the resolution limit of conventional fluorescence microscopy. At present, there are only a few reported studies using superresolution fluorescence microscopy to explore the nanoscale organization of DSB repair foci (13)(14)(15)(16). Those studies revealed that DSB foci consist of several subfoci with a lateral diameter ranging between ;100 and 200 nm.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Despite numerous studies regarding the involvement of gH2AX in DNA repair, the nanoscale organization of gH2AX and DDR proteins within IR-induced foci remains largely unknown because of the resolution limit of conventional fluorescence microscopy. At present, there are only a few reported studies using superresolution fluorescence microscopy to explore the nanoscale organization of DSB repair foci (13)(14)(15)(16). Those studies revealed that DSB foci consist of several subfoci with a lateral diameter ranging between ;100 and 200 nm.…”
mentioning
confidence: 99%
“…Because of its interactions with other NHEJ and non-NHEJ proteins, DNA-PKcs may also act as a scaffold protein to facilitate the localization of DNA-repair proteins to the site of DSBs (36). Unlike several other important DNA-repair proteins, such as, Ku70/80, 53BP1, Rad51, among others (12,14,16), DNA-PK has not yet been analyzed by superresolution microscopy.…”
mentioning
confidence: 99%
“…These steps allow the efficient recruitment of the repair factors to the damaged DNA regions and implicate in the choice between the DNA repair pathways. For examining the DSB-induced chromatin changes, confocal microscopy-based techniques are used in most of the studies, although in the last few years high-throughput chromosome conformation capture technique (4C) and single cell microscopy were utilized to gain detailed insights about the protein interactions and cascades involved in the different repair pathways 31,5357 . A more detailed overview has raised more questions, which could be answered only at a single-cell level: how the different DNA repair pathways are chosen and how individual repair proteins are regulated to access the DNA repair site.…”
Section: Discussionmentioning
confidence: 99%
“…By using these techniques, it was shown that the γH2AX signal distributes up to a megabase around the damaged site 8 generating DNA repair foci with a typical feature size of half a micron, which is just above the resolution limit of traditional fluorescence microscopes. High resolution imaging based datasets of DSB structures have already been published and demonstrated via single molecule localization methods (SMLM) 2328 , structured illumination microscopy (SIM) 26,29,30 , and stimulated emission depletion (STED) 2931 super-resolution methods. These images can be further evaluated by using cluster analysis, and both the spatial distribution and the geometrical parameters of foci and even nano-foci can be determined 32,33 .…”
Section: Introductionmentioning
confidence: 99%
“…It has been known for many years that repair foci demarcate the intracellular locations of recombination intermediates 142,148 , but we know very little about the precise organization and dynamic properties of the proteins, protein complexes and nucleic acid structures that form these foci 148 . A recent study using STED microscopy to study repair foci induced by ionizing radiation 149 demonstrates that SR imaging has the potential to provide a detailed picture of how the nucleoprotein complexes involved in recombination are organized in living cells.…”
Section: Sr-based Insights Into Recombinationmentioning
confidence: 99%